PENERAPAN MODEL PBL PADA PEMBELAJARAN GEOGRAFI DI KELAS XI IPS SMA NEGERI 5 PONTIANAK - Yosefus Ronald Wilson; Sri Buwono; Agus Sugiarto (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine effect of Problem Based Learning models on learning outcomes in learning geography in class XI IPS Senior High School 5 Pontianak. The research method used is a quantitative research method. The research instrument used was a test instrument in the form of multiple choice questions, and a non-test instrument in the form of an interview guide. The results showed that there was a positive influence on the application of the model of problem based learning to student learning outcomes in geography subjects, especially the dynamics of Indonesian population class XI IPS SMA Negeri 5 Pontianak in the form of an increase in average grade grades. This is based on the results of hypothesis testing namely the value of Sig. (2-tailed) of 0.019. So, Ho is rejected or Ha is accepted, because the value of Sig. t-test (2-tailed) which is 0.019 <0.05. The conclusion obtained is that there are differences in student learning outcomes by applying the Problem Based Learning learning model to geographical subjects, especially the material on Indonesian population dynamics using conventional methods.Keywords: Problem Based Learning Model, Geography Learning Outcomes